Structural studies of Von Willebrand Factor regulators for Thrombotic Thrombocytopenic Purpura. - Markham-Lee, Zoe Jade (2024)
Blood clotting requires an urgent and efficient response with von Willebrand factor (VWF) playing a major role through recruitment of platelets forming a haemostatic plug. VWF is a large multi-domain glycoprotein, with the A1 domain for platelet binding via Gp1bα and the A2 domain containing the cleavage site to reduce multimer size. VWF is regulated by A Disintegrin-like And Metalloprotease with Thrombospondin type I repeats, member 13 (ADAMTS13) to maintain the delicate haemostatic thrombotic balance. ADAMTS13 is a highly specific protease, only cleaving VWF at the scissile bond under specific flow conditions. The process by which this regulation is maintained is still unclear, with details on ADAMTS13 latency and subsequent interaction and cleavage of VWF still to be elucidated.